Worldwide hotspots and trends in stem cell therapy for kidney disease in the last decade: a bibliometric and visualization analysis from 2015 to 2024 - Liao, Shengchun; Zhang, Xinyue; Zhou, Yiting; Wang, Lingchen; Chen, Chi; Ye, Chaoyang; Zhou, Yuan; Wang, Chen (Frontiers in Immunology, 2025)
BackgroundKidney disease represents a significant global health concern. Stem cell therapy has gained attention as a potential solution for chronic kidney disease, acute kidney injury, and end-stage renal disease. This study aims to provide a comprehensive overview of the status of stem cell therapy for kidney disease through a systematic review of the literature.MethodsThe literature included in this study was exclusively sourced from the Web of Science Core Collection. CiteSpace, VOSviewer, R-Bibliometrix, and the Literature Data Governance and Analysis System to evaluate factors such as publication quantity, author contributions, institutional involvement, geographic distribution, and keyword usage.ResultsThis study on stem cell therapy for kidney disease included 1,874 articles. A significant number of publications came from China and the United States. The Mayo Clinic had the highest publication output, while Stem Cell Research & Therapy was the leading journal in terms of publication volume. Additionally, Lerman LO was the most prolific author in this field. Currently, there is a growing focus on mesenchymal stem cells and acute kidney injury models in this field. Future research is likely to explore topics such as extracellular vesicle-based therapies, various stem cell types, diabetic nephropathy, and membranous nephropathy.ConclusionThis study applied bibliometric methods to assess the application and development of stem cell therapy for kidney disease over the past decade. It identified key research areas and forecasted future trends. The findings offer valuable insights for guiding future investigations into stem cell therapy for kidney disease.